Effectiveness of animated infographics for enhancing the level of understanding of complex financial information by consumers - Tkachenko, Pavlo (Актуальні питання економічних наук, 2026)
The complexity of financial products and the growth in the volume of economic information highlight the problem of their adequate perception by consumers. Traditional text and static visual formats often do not provide sufficient understanding of financial indicators, risks, and conditions for conscious consumer decision-making, necessitating the search for more effective communication tools. The aim of the article is to evaluate the effectiveness of animated infographics as a means of increasing consumers’ perception of complex financial information and to determine their impact on the cognitive outcomes of this process. Methods. The study is based on a combination of methods: content analysis of scientific sources, comparative analysis of formats for presenting financial information, and empirical evaluation of consumer perceptions of information messages presented in text, static, and animated infographic forms. To summarize the results, methods of logical analysis, systematization and interpretation were used. Results. It was found that the use of animated infographics helps reduce cognitive load, increase the accuracy of interpreting financial indicators, and improve the memorability of key information. Animated visualization provides better structuring of complex data, facilitates the establishment of cause-and-effect relationships and increases the level of consumer involvement in the process of perceiving financial messages. Conclusions. It has been proven that animated infographics are an effective tool for communicating complex financial information and can increase consumers’ financial awareness and improve the quality of economic decision-making. The practical significance of the results lies in their potential application to the marketing communications of financial institutions and to information and educational projects to improve understanding of financial products and increase consumer trust in financial services.